The Influence of Spiritual Quotient on the Formation of Rahmatan lil-‘Alamin Character in SDGs-Oriented Islamic Education - Muhammad Fajrul Falaah; Sugiyo Sugiyo; A. Mufrod Teguh Mulyo (Profetika: Jurnal Studi Islam, 2027)
Objective: This study aims to examine the influence of Spiritual Quotient (SQ) on the formation of Rahmatan lil-‘Alamin character among Islamic high school students in Boyolali Regency and to examine its relevance to SDGs-oriented Islamic education. Theoretical framework: The study is grounded in the concept of spiritual intelligence, which emphasizes spiritual awareness, the search for meaning, self-reflection, and the internalization of religious values, combined with the Rahmatan lil-‘Alamin framework, which emphasizes compassion, tolerance, moderation, justice, and social responsibility. Literature review: Previous studies have generally examined spiritual intelligence as a factor associated with students’ morality, emotional maturity, and prosocial behavior, while Rahmatan lil ‘alamin has frequently been discussed from normative and conceptual perspectives. However, limited empirical research has examined the relationship between spiritual quotient and Rahmatan lil-‘Alamin character as measurable constructs within Islamic secondary education. Method: This research employed a quantitative explanatory approach with a non-experimental design. Data were collected from 85 students selected through purposive sampling from two Islamic high schools in Boyolali Regency using structured questionnaires. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. Results: The results demonstrate that Spiritual Quotient has a positive and significant influence on Rahmatan lil-‘Alamin character, with a path coefficient of 0.546. Students with stronger spiritual awareness, meaningful life orientation, and internalized religious values tend to exhibit greater compassion, tolerance, moderation, and social responsibility. Implications: The findings suggest that strengthening spiritual intelligence can support character education and contribute to SDG 4 (Quality Education) and SDG 16 (Peace, Justice, and Strong Institutions) by promoting inclusive, ethical, peaceful, and socially responsible educational environments. Novelty: This study provides empirical evidence positioning Rahmatan lil-‘Alamin character as a measurable educational construct influenced by spiritual quotient, thereby extending previous normative discussions and strengthening the empirical foundation of SDGs-oriented Islamic education.